2007
DOI: 10.2116/analsci.23.317
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorometric Determination of Kynurenic Acid with Horseradish Peroxidase in the Presence of Hydrogen Peroxide

Abstract: The catalytic activity of horseradish peroxidase (HRP) in the presence of hydrogen peroxide has been investigated for the fluorescent derivatization of kynurenic acid under conditions with no exposure to light. Non-fluorescent kynurenic acid was converted into a fluorescent compound (Ex: 367 nm, Em: 470 nm) with HRP in the presence of hydrogen peroxide, and the optimum conditions of this fluorescent derivatization were investigated. Moreover, this fluorescent derivatization was developed for a spectrofluoromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
12
0
3
Order By: Relevance
“…However, kynurenic acid showed severe interference because kynurenic acid was converted into a fluorescent compound with HRP under the conditions in this study, as described in the previous report. 22) Other substances and ions except for EDTA showed almost no interference.…”
Section: Effects Of Interfering Substancesmentioning
confidence: 96%
See 2 more Smart Citations
“…However, kynurenic acid showed severe interference because kynurenic acid was converted into a fluorescent compound with HRP under the conditions in this study, as described in the previous report. 22) Other substances and ions except for EDTA showed almost no interference.…”
Section: Effects Of Interfering Substancesmentioning
confidence: 96%
“…22) The results indicated that the catalytic activity of HRP in the presence of H 2 O 2 is useful for the derivatization of a nonfluorescent substrate into a fluorescent compound. Accordingly, in the present study, we selected nonfluorescent QA as a substrate of HRP and investigated whether QA could be converted into a fluorescent compound by the catalytic activity of HRP in the presence of excess H 2 O 2 , and whether QA could be determined by measuring the fluorescence intensity of the reaction product.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…1: R2 and R3, COOH), a tryptophan metabolite, were converted into a fluorescent compound by the catalytic activity of HRP in the presence of excess H2O2. 6,7 Moreover, we demonstrated that this fluorescent derivatization could be applied to the determination of trace amounts of kynurenic acid and quinolinic acid in vital fluids. 6,7 Accordingly, in this study, we investigated whether other tryptophan metabolites, such as xanthurenic acid (XA), nicotinic acid (NA), 3-hydroxyanthranilic acid, and picolinic acid ( Fig.…”
Section: Introductionmentioning
confidence: 93%
“…6,7 Moreover, we demonstrated that this fluorescent derivatization could be applied to the determination of trace amounts of kynurenic acid and quinolinic acid in vital fluids. 6,7 Accordingly, in this study, we investigated whether other tryptophan metabolites, such as xanthurenic acid (XA), nicotinic acid (NA), 3-hydroxyanthranilic acid, and picolinic acid ( Fig. 1), will be converted into a fluorescent compound by the catalytic activity of HRP in the presence of excess H2O2.…”
Section: Introductionmentioning
confidence: 93%